Mandatory Arrest Law in domestic violence cases and its implementation in New York City - Milivojević Sanja K. (Temida, 2002)
This paper contains the analysis of the Mandatory Arrest Law in domestic violence cases in New York State. Introduction includes the subject and main goals of the paper. Second chapter starts with historical development of the police response in domestic violence cases in New York before and after the Mandatory Arrest Law is passed, than analysis of the Law, and ends with one of the programs which Safe Horizon, Victim Service organization, developed in New York City. Third chapter gives the analysis of pro et contra arguments for mandatory arrest provision and results of surveys and studies, which were conducted in United States. In fourth chapter we present the analysis of the research conducted in two police precincts in New York City this year. Paper also contains the list of main problems in implementation of this Law in New York City.